1964
DOI: 10.1021/bi00892a001
|View full text |Cite
|
Sign up to set email alerts
|

The Enzymatic Synthesis of D-Alanyl-D-alanine. III. On the Inhibition of D-Alanyl-D-alanine Synthetase by the Antibiotic D-Cycloserine*

Abstract: Inhibitor studies indicate that both D-alanine (A) binding sites of D-alanyl-D-alanine synthetase are sensitive to D-4-amino-3-isoxazolidone (D-cycloserine [I]). The K for the reaction E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
162
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 27 publications
5
162
0
Order By: Relevance
“…A noteworthy property of VRSA-9 Ddl was a lag period in the enzymatic assay (Fig. 3A), a phenomenon not seen in VRSA-6 Ddl or in any other D-Ala:D-X ligase (4,23,27). This kinetic behavior is characteristic of hysteretic enzymes which, during catalysis, slowly convert from one kinetic form to another as a a The cytoplasmic peptidoglycan precursors of VRSA-9 grown with or without vancomycin were analyzed as described previously (22 (13,25).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A noteworthy property of VRSA-9 Ddl was a lag period in the enzymatic assay (Fig. 3A), a phenomenon not seen in VRSA-6 Ddl or in any other D-Ala:D-X ligase (4,23,27). This kinetic behavior is characteristic of hysteretic enzymes which, during catalysis, slowly convert from one kinetic form to another as a a The cytoplasmic peptidoglycan precursors of VRSA-9 grown with or without vancomycin were analyzed as described previously (22 (13,25).…”
Section: Resultsmentioning
confidence: 96%
“…The kinetic parameters of the VRSA-9 Ddl reaction were determined using the ADP release spectrophotometric assay previously described (4,23,27). K m for ATP was measured at a fixed 80 mM concentration of D-Ala. VRSA-9 Ddl was used at a concentration of 1.5 M.…”
Section: Methodsmentioning
confidence: 99%
“…Cycloheximide, kanamycin, and streptomycin are also reported to inhibit the protein synthesis, but they do not inhibit the growth of Gram-positive bacteria (Madigan et al, 2000). Cephalexin and cycloserine inhibit the cell wall synthesis, and mitomycin C inhibits DNA synthesis (Iyer and Szybalski, 1964;Morin et al, 1969;Neuhaus and Lynch, 1964). As mentioned above, antibiotics influence biosyntheses, and induced the cystite formation of A. ureafaciens NRIC 0157 T .…”
Section: Discussionmentioning
confidence: 94%
“…The acyl carbon atom of the acylphosphate then reacts with the amino group of the second D-Ala to yield a tetrahedral intermediate that dissociates to produce phosphate and D-Ala-D-Ala. Kinetic studies have identified two subsites for D-Ala binding in the active site (11,12). Structural (13)(14)(15)(16)(17)(18) and mutagenesis (19) studies have shown that many of the residues involved in substrate binding and catalysis are conserved in the D-Ala:D-X ligase superfamily.…”
mentioning
confidence: 99%